(untitled) (KSV Journal of Pharmacy and Health Sciences, 2025)
This article provides an in-depth analysis of Cardamom (Elettaria cardamomum), known as the “Queen of Spices,” is a highly valued spice with significant culinary, medicinal, and industrial applications. Cardamom is widely cultivated in tropical regions, such as in India, Sri Lanka, and Guatemala, belonging to the Zingiberaceae family. This review highlights the botanical characteristics, phytochemical composition, and therapeutic potential of cardamom. Emphasis is given to its traditional and modern uses in health, culinary, and pharmaceutical domains. It is rich in essential oils, flavonoids, and other bioactive compounds that exhibit antioxidant, antimicrobial, anti-inflammatory, and digestive health-promoting properties. Furthermore, cardamom has demonstrated potential in managing metabolic disorders, cardiovascular health, and certain types of cancer in preclinical studies. The article also discusses cultivation practices, post-harvest processing. Despite its diverse benefits, challenges such as adulteration, sustainability in production, and the need for more clinical research remain. This review aims to provide comprehensive insights into cardamom’s Pharmacognostical Description, Phytochemistry and Analytical Approaches.